The evolution of devices and systems supporting rehabilitation of lower limbs - Olinski, Michał; Lewandowski, Bogusz; Gronowicz, Antoni (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents the process of development, as well as examples of devices and systems supporting rehabilitation of the human lower extremities, developed independently over the years in many parts of the world. Particular emphasis was placed on indicating, which major groups of devices supporting kinesitherapy of the lower limbs can be distinguished, what are the important advantages and disadvantages of particular types of solutions, as well as what directions currently dominating in development of rehabilitation systems may be specified.
Keywords: kinesitherapy; manipulator; biofeedback; interactivity; exoskeleton